Correction: Surface-enhanced Raman scattering on a silver film-modified Au nanoparticle-decorated SiO2 mask array. Issue 86 (18th September 2015) - Chang, Chi-Ching; Chen, Liang-Yih; Yang, Kuang-Hsuan; Chen, Qing-Ye; Liang, Yu-Chih; Lin, Shyr-Yi; Liu, Yu-Chuan
<x xml:space="preserve">Abstract</x> Correction for 'Surface-enhanced Raman scattering on a silver film-modified Au nanoparticle-decorated SiO2 mask array' by Chi-Ching Chang et al., RSC Adv., 2015, 5, 66096–66103.